Family-focused behavioral pediatrics - Coleman, William Lord, 1943-2017 (Core handbooks in pediatrics., 2001)
This first-of-a-kind, pocket-size, easy-to-use manual describes practical, family-oriented approaches for the evaluation and management of common behavioral and interaction problems that are often resistant to child-centered approaches. These problems--e.g., tantrums, sleep problems, non-compliance, parent-child conflict, parenting disagreements, and social-emotional complications of ADHD and learning problems--affect and/or arise in the family. Physicians, nurse practitioners, psychologists, and school counselors can implement these techniques in the office, specifically how to: identify prob.